Engineering design tools for shape memory alloy actuators: CASMART collaborative best practices and case studies. (November 2019) - Wheeler, Robert W; Benafan, Othmane; Calkins, Frederick T; Gao, Xiujie; Ghanbari, Zahra; Hommer, Garrison; Lagoudas, Dimitris; Martin, Daniel; Nicholson, Douglas E; Petersen, Andrew; Phillips, Francis R; Stebner, Aaron P; et al.
One of the primary goals of the Consortium for the Advancement of Shape Memory Alloy Research and Technology is to enable the design of revolutionary applications based on shape memory alloy technology. To advance this goal and reduce the development time and required experience for the fabrication of shape memory alloy actuation systems, several modeling tools were developed for common actuator types and are discussed along with case studies, which highlight their capabilities and limitations. Shape memory alloys have many potential applications as reliable, lightweight, solid-state actuators given their ability to sustain high stresses and recover large deformations. In this article, modeling frameworks are developed for three common actuator designs: wires, lightweight, low-profile, and easily implemented; coiled springs, offering actuation strokes upward of 200% at reduced mechanical loads; and torque tubes, which can provide large actuation torques in small volumes and repeatable low-load actuation. Although the design and integration of a shape memory alloy–based actuation system requires application- and environment-specific engineering considerations, common modeling tools can significantly reduce the investment required for actuation system development and provide valuable engineering insight. This analysis presents a collection of Consortium for the Advancement of Shape Memory Alloy Research and Technology collaborative best practices to allow readers to utilize the available design tools and understand their modeling principles.